Backward-looking analysis - Mathias Dolls; Richard Lewney (Office for Official Publications of the European Communities, 2017)
We develop a new modelling approach combining micro and macro simulations to analyse distributional and stabilizing effects of a European Unemployment Benefit System (EUBS). We run counterfactual simulations based on micro data for the period 1995 to 2013 to estimate net contributions for different variants of EUBS across European member states. Our micro estimates are then used to feed the macro-econometric model in order to obtain counterfactual evolutions of income and unemployment. These new income and employment series are finally simulated again at the micro level. We compare results before and after taking account of the macroeconomic feedback effects and analyse the difference that the feedback effects make.
Additional information: This paper was written as part of Task 3B for the research project 'Feasibility and Added Value of a European Unemployment Benefit Scheme' (contract VC/2015/0006).
Keywords: F55; H23; J65; 330; European fiscal integration; unemployment insurance; automatic stabilizers; Europäisches Arbeitsrecht; Arbeitslosenversicherung; EU-Finanzbeziehungen; Verteilungswirkung; Mikroökonomik; Makroökonomisches Modell; Simulation; EU-Staaten